PRESCRIBING DATA ANALYSIS BASED ON ELECTRONIC PRESCRIPTION IN COMMUNITY HEALTH CENTER IN GUNUNGKIDUL - Zakiyah Oktaviani; Lutfan Lazuardi; Hari Kusnanto (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Community Health Center is one of the government’s efforts in providing health services in the community. Information system is very crucial in organizing community health centers in order to manage operational activities effectively. Monitoring the results of management information systems, especially in electronic prescription needs to be studied, viewed from the prevention of medication errors, duplication of drug therapy, and drug interactions. The study was conducted by collecting data from the electronic prescription of 10 disease with highest prevalence in 2011 with a sample of 1200 prescription. This research was non-experimental descriptive using retrospective method. Data were taken by random sampling.  The use of information systems, especially in electronic prescribing in general, can prevent medication error. Duplication of therapy in prescribing occurred in 16 prescription. Drug interactions occured in 48 prescription. Evaluation of the results of the overall prescribing showed that there was a trend in the use of corticosteroids drugs.Keywords: management information systems, electronic prescribing, public health of Gunung Kidul.